An inflection point in European Union studies?. Issue 8 (13th September 2016) - Young, Alasdair R.
ABSTRACT: This contribution introduces a selection of the best papers presented at the 2015 European Union Studies Association's biennial conference. It uses these papers as a jumping off point to consider whether European Union (EU) studies suffers the same 'gap' with real-world problems that is seen to afflict some portions of the academy and to ask whether EU studies is at an inflection point. It argues that EU studies are closely linked to the substance of the European project. It identifies how the contributions to this collection speak to different aspects of the EU: closer co-operation; policy-making within a 'normal' political system; the implications of European integration for its member states. Given this link between the substance of the European project and the focus of EU studies, this contribution argues that the challenges currently confronting the EU – the lingering eurozone debt crises; the migrant/refugee crisis; the prospect of a British exit; and recent terrorist attacks – may mark an inflection point in EU studies. The reason is that for the first time 'less Europe' has emerged as a serious option in response to crisis. This possibility reignites questions of (dis)integration and calls into question the assumption the EU policy only accumulates.